Ertapenem for the treatment of bloodstream infections due to ESBL-producing Enterobacteriaceae: a multinational pre-registered cohort study. (22nd February 2016) - Gutiérrez-Gutiérrez, Belén; Bonomo, Robert A.; Carmeli, Yehuda; Paterson, David L.; Almirante, Benito; Martínez-Martínez, Luis; Oliver, Antonio; Calbo, Esther; Peña, Carmen; Akova, Murat; Pitout, Johann; Origüen, Julia; et al.
Abstract: Objectives: Data about the efficacy of ertapenem for the treatment of bloodstream infections (BSI) due to ESBL-producing Enterobacteriaceae (ESBL-E) are limited. We compared the clinical efficacy of ertapenem and other carbapenems in monomicrobial BSI due to ESBL-E. Methods: A multinational retrospective cohort study (INCREMENT project) was performed (ClinicalTrials.gov identifier: NCT01764490). Patients given monotherapy with ertapenem or other carbapenems were compared. Empirical and targeted therapies were analysed. Propensity scores were used to control for confounding; sensitivity analyses were performed in subgroups. The outcome variables were cure/improvement rate at day 14 and all-cause 30 day mortality. Results: The empirical therapy cohort (ETC) and the targeted therapy cohort (TTC) included 195 and 509 patients, respectively. Cure/improvement rates were 90.6% with ertapenem and 75.5% with other carbapenems ( P = 0.06) in the ETC and 89.8% and 82.6% ( P = 0.02) in the TTC, respectively; 30 day mortality rates were 3.1% and 23.3% ( P = 0.01) in the ETC and 9.3% and 17.1% ( P = 0.01) in the TTC, respectively. Adjusted ORs (95% CI) for cure/improvement with empirical and targeted ertapenem were 1.87 (0.24–20.08; P = 0.58) and 1.04 (0.44–2.50; P = 0.92), respectively. For the propensity-matched cohorts it was 1.18 (0.43–3.29; P = 0.74). Regarding 30 day mortality, the adjusted HR (95% CI) for targeted ertapenem was 0.93 (0.43–2.03; P = 0.86) and for the propensity-matched cohorts it was 1.05 (0.46–2.44; P = 0.90). Sensitivity analyses were consistent except for patients with severe sepsis/septic shock, which showed a non-significant trend favouring other carbapenems. Conclusions: Ertapenem appears as effective as other carbapenems for empirical and targeted therapy of BSI due to ESBL-E, but further studies are needed for patients with severe sepsis/septic shock.